Mechanistically guided one pot synthesis of phosphine-phosphite and its implication in asymmetric hydrogenation - Sen, Anirban; Kumar, Rohit; Pandey, Swechchha; Raj, K. Vipin; Kumar, Pawan; Vanka, Kumar; Chikkali, Samir H. (European Journal of Organic Chemistry, 2022)
Although hybrid bidentate ligands are known to yield highly enantioselective products in asymmetric hydrogenation (AH), synthesis of these ligands is an arduous process. Herein, a one pot, atom-economic synthesis of a hybrid phosphine-phosphite (L1) is reported. After understanding the reactivity difference between an 0-nucleophile versus C-nucleophile, one pot synthesis of Senphos (L1) was achieved (72%). When L1 was treated with [Rh], P-31 NMR revealed bidentate coordination to Rh. Senphos, in the presence of rhodium, catalyzes the AH of Methyl-2-acetamido-3-phenylacrylate and discloses an unprecedented turn over frequency of 2289, along with excellent enantio-selectivity (92%). The generality is demonstrated by hydrogenating an array of alkenes. The AH operates under mild conditions of 1-2 bar H-2 pressure, at room temperature. The practical relevance of Ll is demonstrated by scaling-up the reaction to 1 g and by synthesizing DOPA, a drug widely employed for the treatment of Parkinson's disease. Computational insights indicate that the R isomer is preferred by 3.8 kcal/mol over the S isomer.
Keywords: asymmetric hydrogenation; catalysis; DOPA synthesis; One pot synthesis; Phosphine-phosphite ligand